THE IMPACT OF RISING FOOD PRICES ON FARMERS’ WELFARE IN INDONESIA - Albertus Girik Allo; Elan Satriawan; Lincolin Arsyad (Journal of Indonesian Economy and Business (JIEB), 2018)
Food prices regularly change due to various factors such as the policy on imports. This paper analyzes the impact of changes in food prices including rice, red onions, and garlic, on farmers’ welfare. The Quadratic Almost Ideal Demand System (QUAIDS) was used to estimate the demand function for food commodities, and the Compensating Variation (CV) was used to estimate the impact of price changes both immediately and in the short-term. This study contributes an idea of how the government makes its policies on food prices and imports, and how they provide benefits for farmers in Indonesia. Data were collected from the 2014 National Socio-economic Survey (SUSENAS). The research results indicated that income improvement led to the increase in rice, red onion and garlic consumption. The dynamics of income, own-price and cross-price elasticity varied, depending on demography, the social economic condition, and the geographic location of the household. The short-term impact of imported products on welfare changes was larger than the immediate impact.